Heritage Preservation Education for the General Public – The role of Hands-on Education - Lobovikov-Katz, Anna; Moropoulou, Antonia; Konstanti, Agoritsa; Lampropoulos, Kyriakos (Technical Annals, 2022)
Heritage education for the general public by conservation experts is the key to success in preserving the world cultural heritage. An extended State-of-the-Art Review on educational activities for the general public on conserva-tion of cultural heritage (CCH) was undertaken in 2009, as part of the European Project ELAICH (Educational Linkage Approach In Cultural Heritage). Its re-sults have not yet been published. This article revisits some selected data from the conclusions of the Review, drawn up by the leading partner of the project, with a glimpse into some present aspects of heritage education, concentrating specifically on educating the general public in CCH.